Вибір схем та оцінки трансформації свердловин Єфремівського родовища в геотермальні сайти енергогенерації - Михайленко, Аліна; Фик, Михайло Ілліч (Національний технічний університет "Харківський політехнічний інститут", 2023)
The paper analyzes the key issues and aspects of the conversion and use of an old high-rate well as a geothermal well for the conditions of the massive deposit of the Yefremivske field of Ukraine, proposes a formula for preliminary assessment of geothermal resources of oil and gas deposits on the specific example of an oil and gas well of this field, the adequate estimated resource potential of the discovered massive productive reservoir is confirmed, it is proved that in the conditions of geological productive deposits of the field, the most profitable is the direct and binary scheme of heat and electricity utilization by local energy consumers. The urgency of the problem. The use of geothermal sources in gas and gas condensate fields can ensure stable and sustainable energy production. Objective. The aim of this work is to assess the prospects for the extraction of geothermal energy from the productive reservoir of the Yefremivske field, to quantify the heat production of the selected high-rate well in units of natural gas production, and to predict the adaptation of the technological scheme of the process of extracting geothermal energy from the opened massive reservoir. Methods and equipment. Modern scientific researches in the field of geothermal energy are analyzed, mathematical and geological methods are used to assess the potential of geothermal reserves, data and results of gas condensate field development projects are used. Results. The conversion of a high-flow well to a geothermal fund can be accomplished by using additional geothermal heat exchangers in the separation system and a closed circulation circuit of produced water. According to the capacity calculations, a potential well can be converted to the geothermal fund and provide relatively high heat output in the direct and binary scheme of the formed power generation site. In particular, it is shown that the closed circulation of geothermal waters through a duplet of high-rate wells that have uncovered a massive productive gas condensate deposit of the Yefremivske field provides thermal energy productivity of about 15 MW, which is equivalent to the production of 32 thousand m3/day of natural gas of standard caloric content. Scientific value of the development. Introduction of information about the Yefremivske field and parameters of its massive productive reservoir into scientific circulation. The obtained data contribute to the understanding of transformation processes and improve the technical capabilities of converting gas wells into stable geothermal energy sources. Practical significance. The use of old gas condensate wells in geothermal energy will help reduce greenhouse gas emissions, as well as ensure the sustainability of energy supply in the region, and provide tens of megawatts of thermal power. This can serve as an example for other regions with large gas and gas condensate fields.

У роботі проаналізовано ключову проблематику та аспекти переведення та використання старої високодебітної свердловини у якості геотермальної для умов масивного покладу Єфремівського родовища України, запропоновано формулу попередньої оцінки геотермальних ресурсів нафтогазових покладів на конкретному прикладі нафтогазової свердловини цього родовища, підтверджено адекватний оцінений ресурсний потенціал розкритого масивного продуктивного покладу, доведено – в умовах геологічних продуктивних покладів родовища найвигіднішою є пряма та бінарна схема утилізації тепла та електрики місцевими споживачами енергоресурсів. Актуальність проблеми. Використання геотермальних джерел у газових та газоконденсатних родовищах може забезпечити стабільне та стале виробництво енергії. Мета. Метою даної роботи є оцінка перспектив вилучення геотермальної енергії з продуктивного покладу Єфремівського родовища, кількісна оцінка теплопродуктивності обраної високодебітної свердловини в одиницях видобування природного газу, прогноз адаптації технологічної схеми процесу вилучення геотермальної енергії з розкритого масивного покладу. Методи і апаратура. Проаналізовано сучасні наукові дослідження у галузі геотермальної енергії, залучені математичні та геологічні методи для оцінки потенціалу геотермальних резервів, залучено дані та результати проектів розробки газоконденсатного родовища .
Selection of Schemes and Evaluation of Transformation of Wells of the Efremivske Field Into Geothermal Power Generation Sites
Keywords: geothermal energy; wells re-injection; energy potential; renewable energy sources; geothermal reserves of oil and gas deposits; Yefremivske gas condensate field; геотермальна енергія; переведення свердловин; енергетичний потенціал; відновлювані джерела енергії; геотермальні резерви нафтогазових покладів; Єфремівське газоконденсатне родовище